Corrosion and materials in the oil and gas industries - Javaherdashti, Reza; Nwaoha, Chikezie, 1984-; Tan, Henry, 1970- (Boca Raton, FL : Taylor & Francis, 2013)
'With numerous case studies, this book addresses key corrosion issues in the oil and gas industry and discusses strategies and technology for preventing and controlling corrosion. It gives an up-to-date account of corrosion management, covering identification, prevention, and mitigation. Experts from various science and engineering fields explain the chemical causes of corrosion and describe control methods and techniques to monitor corrosion. They also focus on corrosion hazards, tests, and analysis'--
Includes bibliographical references and index.
Keywords: Petroleum engineering -- Equipment and supplies -- Protection; Petroleum industry and trade -- Equipment and supplies -- Corrosion; Petroleum engineering -- Materials; Corrosion and anti-corrosives.